THE EFFECT OF TOPOGRAPHICAL DIFFERENCES ON THE GROWTH OF KOI CARP (Cyprinus carpio koi) - Halimah, Nur; Jailani, Abdul Qadir; Sari, Annisa Novita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Interest in the cultivation of koi carp commodities has increased during the Covid-19 pandemic. Breeders come from various communities. This study aims to determine whether topographic differences have an effect or not on the growth of koi carp. The research was conducted from February to March 2022 for 45 days. The location of the research was carried out in three different places, Kaliangkrik, Tempuran, and Kebumen. The research method used was a Completely Randomized Design (CRD) with 3 treatments and 3 repetitions. The first treatment is an altitude of 1,030 meters above sea level (Kaliangkrik), the second is 323 meters above sea level (Tempuran), and the third is 26 meters above sea level (Kebumen). The data were analyzed using the Analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) further tests. The results showed that topographic differences affect the growth of koi fish both in weight and length growth of koi fish. The altitude that produces the best growth in this study is at an altitude of 26 meters above sea level or located in Kebumen. This is supported by the data showing the highest weight (average 4,1 g), the longest (average 2.5 cm), the lowest FCR (average 2,16), and the highest Survival Rate (SR) high (80%).